The relationship between regulatory focus and online shopping – perceived risk, affect, and consumers' response to online marketing. (1st January 2012) - Atorough, Peter; Donaldson, Bill
Regulatory focus theory (RTF) has demonstrated that individuals can be distinguished on the basis of two independent structures of strategic inclination and orientation in the pursuit of goals: promotion focus – which emphasises the presence of positive outcomes while minimising errors of omission, versus prevention focus – which favours the absence of negative outcomes and minimising errors of commission. Yet no research, thus far, has explicitly considered the potential link between consumers' regulatory focus (RF), perceived risk, affect, and their response to online marketing (ROM) in the various dimensions of online shopping (OS). This paper fills this gap. By linking regulatory focus with online consumer shopping behaviour we empirically test a number of hypotheses to predict how consumers with different foci perceive risk on the internet, the consequence of this perception on their affect, and their overall response behaviour to online marketing. Our findings provide confirmatory evidence that RF is a powerful predictor of behaviour in OS.